The genesis of exceptionally thick shallow marine sequences exposed within the South Munster Basin of southern Ireland - Quin, Jamie G. (Trinity College (Dublin, Ireland). Department of Geology, 2002)
The South Munster Basin (southern Ireland) is an E-W trending fossil rift system that was active during the Late Devonian and Early Carboniferous. Subsidence during this period was rapid and led, despite a high sediment flux, to transgressive replacement of continental by shallow then deeper marine settings. One of the most striking features about the resultant succession is that it includes unusually thick paralic and shallow marine sequences (often > 1km) and these in turn contain exceptionally thick sandstone rich packages (often > 300m). Although these superficially resemble prolonged episodes of continuous sedimentation, detailed logging of 19 coastal sections (~ 5.2 km vertical section) indicates that these packages are actually composed of numerous small-scale sequences each separated by a sequence boundary. What is unusual about this sequence therefore, is that individual sequences are stacked in space over many cycles of relative sea-level change and are not, as is more commonly found, widely distributed. The main control upon this stacking pattern is thought to have been the juxtaposition of a rapidly subsiding basinal area with an isostatically stable basin margin region as this pinned the maximum landward extent of the coastline during successive cycles of relative sea-level change. Other factors that may have contributed to this style of accumulation include minimal basin margin uplift, a large and mature sediment flux, transverse sediment delivery, low shelf gradients and the change in orientation of the basin margin in this region.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin